2014
DOI: 10.2514/1.a32554
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Boundary-Layer Instabilities due to Near-Critical Roughness

Abstract: Measurements of instability and transition were obtained in the wake of a cylindrical roughness within the laminar nozzle-wall boundary layer of the Purdue Mach-6 Quiet Tunnel. Using wall-mounted pressure transducers along the wake centerline, the root-mean-square pressure and power spectra were computed to find evidence of instabilities within the roughness wake. The roughness height was adjusted to explore the case of incipient transition on the nozzle wall. It appeared that small variations in the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…According to the measurements by Wheaton and Schneider, 37 the nozzle wall boundary layer remains completely laminar at k = 2.54 mm and, hence, that case corresponds to a subcritical roughness height. Measurements indicated that k = 2.79 mm (Re kk = 355) may be regarded as a near-critical height since, for this height, incipient transition is observed near the downstream end of the apparatus.…”
Section: A M = 595 Nozzle Roughnessmentioning
confidence: 85%
See 3 more Smart Citations
“…According to the measurements by Wheaton and Schneider, 37 the nozzle wall boundary layer remains completely laminar at k = 2.54 mm and, hence, that case corresponds to a subcritical roughness height. Measurements indicated that k = 2.79 mm (Re kk = 355) may be regarded as a near-critical height since, for this height, incipient transition is observed near the downstream end of the apparatus.…”
Section: A M = 595 Nozzle Roughnessmentioning
confidence: 85%
“…The first roughness configuration models the experiment by Wheaton and Schneider 37 for roughness heights that are post critical but well below the effective roughness height. The roughness element consists of a 5.97 mm diameter micrometer head that is mounted vertically at a distance of x = 1.924 meters from the nozzle throat in the BAMQT at Purdue University (Fig.…”
Section: A M = 595 Nozzle Roughnessmentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive summary of experimental work, which focuses on roughnessrelated transition in hypersonic boundary layers on blunt bodies, is given by Reda 8 and Schneider. 15 The mechanisms leading to transition behind a three-dimensional roughness are only partly understood, but work on mainly super-and hypersonic roughness-induced transition (carefully conducted experiments, 16,17 extensive DNS simulations [18][19][20][21][22] and results from global, 23 two-dimensional linear eigenvalue (LST-2D) [24][25][26][27] and three-dimensional parabolized (PSE-3D) 18,28 instability analyses) have considerably increased the knowledge in the recent years. However, most investigations have been performed on flat plates with a zero pressure gradient (ZPG) and a detailed study on the influence of different pressure gradients on roughness wake-flow instabilities is still missing.…”
Section: Introductionmentioning
confidence: 99%